Nghiên cứu công nghệ trích li dần cám bằng dung môi từ nguồn dầu mỏ trong nước - Cao, Văn Hùng (2011)
Tác giả: Cao Văn Hùng, KS; Nguyễn Thị Ngợi, KS; Trần thị Hòa, KS; Trần Văn Dũng -- Từ khóa: Trích ly; Dần cám; Dầu mỏ